A qualitative approach to explore the cognitive processes used by members of an adult learn-to-cycle program - Franks, Caitlyn; Reis, Arianne C.; Peel, Nicole; Steel, Kylie Ann (Frontiers in Sports and Active Living, 2024)
Introduction Attaining movement proficiency under various constraints is well-researched; of particular interest here is how conscious processing and self-consciousness influence learning and performance. Current research relevant to these variables e.g., reinvestment, tends to utilize quantitative methods and thus overlooks a potentially rich source of understanding. Therefore, the purpose of this study was to apply a qualitative approach to explore the cognitive processes and self-consciousness within a less practiced population of adults participating in a non-competitive leisure activity. Methods To achieve this, eleven semi-structured interviews were conducted with adult women learning or relearning to ride a bicycle. Results Using thematic analysis, two distinct themes were evident and corroborated those illustrated in scales such as the movement-specific reinvestment scale. These themes included Conscious Processing, Recalling Experiences and Movement Analysis, in addition to Style of Movement, and Self-Consciousness. Anxiety also emerged as an additional and relevant theme to learning a new complex movement skill. Discussion The findings indicated that participating women attuned to their movements to the extent that there was a conscious attempt to control their movements, but less so regarding movements being altered by self-awareness. Whilst further research is required, qualitative methods provide a promising basis for exploring the cognitive process involved with the conscious process involved in learning.